Chemoenzymatic Saccharification of Artocarpus heterophyllus Lam. (Jackfruit) Peel Waste and its Utilization for Bioethanol Production - Dharamveer,; Basu, Soumya; Gupta, P. K.; Rana, Vikas; Kumar, Pradeep (Indian Forester, 2019)
Cellulose and hemicelluloses are the most abundant renewable bio-macromolecules found in the biosphere. Bioethanol has received special attention worldwide due to gradual depletion and increasing price of fossil fuels. Bioethanol from cellulosic biomass has gained popularity because of convenience in processing and economic nature. In the present study, chemo-enzymatic saccharification of jack fruit peel waste was employed which yielded upto 30.58 g/L of reducing sugar. Fermentation was carried for bioethanol production by using filtrates of treated jackfruits peel extract with Saccharomyces cerevisiae. Bioethanol yield was monitored throughout a fermentation period of 5 days; bioethanol yield was found to be a maximum of 3 g/L from jack fruit peel waste hydrolysate after distillation. The use of jackfruits peel for the production of bioethanol shall provide with a novel perspective to recycle organic wastes for renewable energy.